2021
DOI: 10.5194/isprs-archives-xlvi-m-1-2021-79-2021
|View full text |Cite
|
Sign up to set email alerts
|

A New Indoor Lidar-Based MMS Challenging Complex Architectural Environments

Abstract: Abstract. The use of moving devices equipped with range- and image-based sensor, generically defined Mobile Mapping systems (MMS), have been quite a disruptive innovation in the development of Geomatics techniques for 3D surveying large indoor-outdoor spaces and offer multiple solutions. The recent expansion of portable devices in the form of trolleys, backpacks, handheld tools largely implements SLAM (Simultaneous Localization and Mapping) algorithms and technology based on both Lidar and/or visual solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This is useful for pre-positioning the scan data during the moving acquisition progression. The actual range-based acquisition is based on the combination of two different scans typology: the long-interval scans and the anchor scans [ 44 ]. If the former is represented by the acquisition of the standard static scans (with tens of minutes scanning and RGB captured data), the latest is a faster version of a static scan, performed along the trajectory characterised by short duration and lower densities, according to the setting parameters (without RGB captured data in the present research release but implemented in current system configuration).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is useful for pre-positioning the scan data during the moving acquisition progression. The actual range-based acquisition is based on the combination of two different scans typology: the long-interval scans and the anchor scans [ 44 ]. If the former is represented by the acquisition of the standard static scans (with tens of minutes scanning and RGB captured data), the latest is a faster version of a static scan, performed along the trajectory characterised by short duration and lower densities, according to the setting parameters (without RGB captured data in the present research release but implemented in current system configuration).…”
Section: Methodsmentioning
confidence: 99%
“…The Swift scans processing reported the following accuracy statistics on hall C (earlier test in hall B reported in [ 44 ] and synthesised in Table 5 ): ICP registration of the anchor scans block: 5 mm accuracy (47% <4 mm) (dataset II). ICP registration of (II) with Mobile scan 7 mm (dataset III).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile mapping systems (MMS) are widely used technology for spatial data collection of large-scale projects like city mapping and they function by equipping moving devices with laser scanning or imaging sensors, which can also be used for built heritage documentation (Alsadik & Jasim, 2018;Bonfanti et al, 2021), even in underground scenarios where TLS are scarcely used due to limited accessibility and non-uniform lighting condition (Di Stefano et al, 2021). Besides MMS, recent studies showed that other LiDAR technologies have been used to document Forgotten Cultural Heritage, such as TLS or Airborne LiDAR sensors (ALS) (Maté-Gonzalez et al, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…In this constantly evolving scenario, the introduction of new methods of documentation and recording of the morphometric characteristics, through the use of MMS survey methodologies, have strongly influenced the activities related to the monitoring of cultural heritage that require a continuous collection of threedimensional data. The use of these devices constitutes a real innovation in the Geomatics sector and the undisputed value of mobile mapping systems is the possibility of significantly accelerating the data acquisition and processing phases (Bonfanti, 2021). The researches on the subject are manifold and show a variety of hardware solutions, with dynamic acquisition procedures through the use of trolleys, backpacks, trolleys, and software.…”
Section: Related Workmentioning
confidence: 99%